The effects of prepubertal epididymal ligation upon androgen receptor distribution in the rat caput epididymis - Gur, F. M.; Timurkaan, S.; Timurkaan, N. (Czech Academy Agricultural Sciences, 2011)
The aim of the present study was to investigate the androgen receptor (AR) distribution in epididymal cells of developing rats and the effects of prepubertal epididymal obstruction upon AR distribution in the rat caput epididymis. At 15 days of age, the young rats were divided at random into groups for epididymal ligation or sham operation. In the ligation group the corpus epididymides were ligated bilaterally; in the sham group only laparatomy was performed. Both groups were sacrificed at 21, 56, 90, 120 days. The epididymes were removed, fixed in Bouin's fixative and embedded in paraffin wax. The tissues were sectioned at 5 mu m and stained using the microwave stimulated antigen retrieval technique for immunohistochemistry. The features of the immunohistochemical staining of caput epididymal cells for the AR were similar across both groups. The operation did not affect AR distribution in caput epididymis. Positive immunohistochemical staining for the AR appeared in nuclei but not in the cytoplasm of caput epididymal cells at all ages beginning from 21 to 120 days old. The staining intensity of AR-positive cells did not change depending on age. In the caput epididymis, immunostainable AR were found in tubular epithelial cells (principal cells, basal cells and apical cells) and interstitial stromal cells (peritubular smooth muscle cells). There were no significant histological alterations in epididymal epithelium.
Keywords: androgen receptor; immunohistochemistry; epididymal ligation; epididymis; rat